Improving interchanges in China: the experiential phenomenon. (January 2015) - Hickman, Robin; Chen, Chia-Lin; Chow, Andy; Saxena, Sharad
Highlights: Surveys are used from three HSR interchanges in China. Expected and realised facilities are compared. Instrumental, attitudinal and affective factors are important to the experience of the journey. Abstract: This paper examines the development of multimodal passenger rail hubs as part of the high-speed rail (HSR) network in the People's Republic of China (PRC). The instrumental, attitudinal and affective experience of the journey through the interchange is assessed from the user perspective. Surveys are used from three HSR stations: Beijing South, Chengdu East and Suzhou North ( N  = 150), representing three types of HSR stations, i.e. national capital, regional capital and sub-regional city. 'Expected' and 'realised' facilities are compared – with the difference representing the 'disgruntlement' factor (after Stradling et al., 2007). The unprecedented urbanisation process currently being witnessed in the PRC, together with the rapid development of the HSR network and associated multimodal interchanges, offers much opportunity to develop a leading-edge public transport system and urban development predicated on the use of public transport. Although the importance of intermodal interchange hubs is being increasingly recognised, the journey experience through the interchange often remains poor, with problems including Wi-Fi availability, waiting and seating, the availability of door-to-door ticketing, crowdedness, access to the hub, time of travel through and waiting in the hub. MANOVA analysis and factorial (three way) MANOVA analysis are used to explore the differences between intermodal hubs, with many instrumental and particularly attitudinal and affective factors being significantly influenced by location.